Pengaruh Metode Suggestopedia terhadap Keterampilan Berbahasa AUD - Hidayanah, Lorient Meyse; Arkam, Rohmad; Mustikasari, Rizki (STKIP PGRI Ponorogo Press, 2023)
Early Childhood Education is an effort made by educational institutions to provide care services that focus on the physical and psychological development of early childhood. The environment built in early childhood education institutions is also adjusted so that children can explore in order to fulfill their development which involves all aspects of development. One aspect of development that is important to develop is the language aspect, where children will use language as a medium to communicate and interact with their environment. The aim of this research is to find out the influence of a method called the suggestopedia method on the language skills of early childhood at Aisyiyah Sambit Kindergarten, Ponorogo Regency. The suggestopedia method is a relaxation method that relies on a person’s subconscious mind to receive material. The subjects of the research carried out were vulnerable early childhood children aged 4-5 years at the Aisyiyah Sambit Kindergarten, totaling 12 children. The method used by researchers is a quantitative method. Based on the research conducted, hypothesis testing shows differences in the average and significance values of the values before and after applying the suggestopedia method. Therefore, the conclusion of this research is that H0 is rejected and Ha is accepted. This means that there is an influence of the suggestopedia method on the language skills of early childhood at Aisyiyah Sambit Kindergarten.